Predictive value of inflammatory burden index for new-onset atrial fibrillation in STEMI patients - Liu, Kun; Tao, Zhiwen; Li, Gonghao; Li, Mingzhu; Yin, Jiayu; Zhou, Lei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe inflammatory burden index (IBI) is a novel and useful inflammatory marker. However, the association between IBI and new-onset atrial fibrillation (NOAF) in patients with ST-segment elevation myocardial infarction (STEMI) remains unclear. This study focuses on exploring the predictive ability of IBI for NOAF after percutaneous coronary intervention (PCI) in STEMI patients.Materials and methodsThis study is a single-center retrospective observational study. Patients diagnosed with STEMI and undergoing primary PCI between October 2022 and February 2025 were continuously enrolled. All enrolled patients received continuous electrocardiogram (ECG) monitoring (>72 h) and were grouped according to whether NOAF occurred during hospitalization. Logistic regression analysis was used to identify potential risk factors for NOAF. Meanwhile, restricted cubic spline (RCS) analysis was employed to thoroughly investigate the possible dose-response relationship between IBI and NOAF.ResultsA total of 696 STEMI patients were finally included in this study. The incidence of NOAF during hospitalization was 62/696 (8.9%). After adjusting for potential confounding factors, the results of multivariate logistic regression analysis showed that left ventricular ejection fraction (OR = 0.928, 95% CI: 0.895–0.962), age (OR = 1.048, 95% CI: 1.022–1.075), and IBI (OR = 1.007, 95% CI: 1.003–1.011) were independent factors for NOAF in STEMI patients (P < 0.05). RCS results suggested that there was a non-linear dose-response relationship between IBI and NOAF. After integrating IBI, the ability of the new model to predict NOAF was significantly improved (NRI = 0.617, 95% CI: 0.360–0.873, P < 0.01; IDI = 0.026, 95% CI: 0.007–0.046, P = 0.008).ConclusionsElevated IBI is an independent risk factor for NOAF after PCI in STEMI patients. Integrating IBI can improve the risk stratification for NOAF in STEMI patients.